2014
DOI: 10.9790/5933-0440111
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Investigation of Short runs IPO underpricing: Evidence from Dhaka Stock Exchange

Abstract: This paper investigates empirical existence of theories of IPO underpricing in Bangladesh. The study based on IPO listed at Dhaka Stock Exchange (DSE) from 2003 to 2013 analyses Level of IPO underpricing and its determinants. OLS regression is used to distinguish the relationship between various independent variables with dependent variable-level of underpricing. The result reveals that market capitalization, underwriter's reputation, oversubscription rate, offer size, float, ownership retention and method of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…An intriguing observation is that the ratio of overpriced issues to underpriced issues in each route remains almost the same (37.5:62.5). The results are consistent with Islam (2014). Some investors made a profit for themselves on the first trading day, while others could not do so.…”
Section: Findings and Discussionsupporting
confidence: 85%
“…An intriguing observation is that the ratio of overpriced issues to underpriced issues in each route remains almost the same (37.5:62.5). The results are consistent with Islam (2014). Some investors made a profit for themselves on the first trading day, while others could not do so.…”
Section: Findings and Discussionsupporting
confidence: 85%
“…Haque et al (2021) found that high earnings forecasting error has resulted in the worst longrun stock performance in the Bangladesh stock market. Initial high return is commonly known as underpricing of IPOs which is studied by Islam (2014) and found that there are numerous reasons for such phenomenon in Bangladesh. The underwriter's reputation, issue size, offer price, etc.…”
Section: Literature Reviewmentioning
confidence: 99%